semantic practices in the book of Thimar AL kuloub (Journal of Human Sciences, 2020)
This research   addresses the most significant semantic issues in the-book  ofThimar AL-kuloub by AlThaalbi, such as the idea of ​​semantic fields, the context of the situation, the question of Collocation, as well as the issue of semantic transformation, and the semiology of topic. Contemporary reflects the extent of the contribution made by Thaalbi in  semantic research. The research problem lies in a central question: Are there any  semantic practices in the book of Thimar ALkuloub  that are close to modern semantic theories?The research section includes an introduction, five demands and a conclusion.